Dampu Awang Legends and Its Contemporary Perception of Indonesian (Javanese) Muslim Against Chinese - Budiyanto, Ary; Latifah (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2019)
Dampu Awang is a legendary figure who is always mentioned in various legends about Cheng Ho/Zheng He on Java. By looking at these legends in the current context, this article re-reads the figure of a legend who was always attached to this figure of Cheng Ho as a reflection of the stereotypical perception of Javanese people towards the Chinese in relation to Islam and Java (Indonesia). An image that existed long ago until now, namely as a creature full of paradox and ambiguity: from being admired and respected to being hated and reviled. This article was closed with a reflection of the relations between China, Islam and Java during the Post Reformation which represented Cheng Ho as the carrier of peaceful Islam.